Scientific substantiation of the model of the drugs' recommended list development for pharmacotherapy of acute bronchitis in children of early age - Kotvitska, Alla; Korobova, Ewgenia (ScienceRise: Pharmaceutical Science, 2017)
Ensuring of the implementation of health sector social standards, in particular, in the aspect of pharmaceutical maintenance of decreed categories of people with free medicines within the regulated list is an important direction of the state policy realization of every country. Aim. Development of the method for the formation of the recommended list of the basic remedies for early age children and its processing on the model of pharmacotherapy of acute bronchitis. Methods. System and analytical methods, as well as multi objective optimization problems solution and hierarchy analysis methods were used for the study. Results. On the basis of systematization of the obtained results of regulatory, marketing and pharmacoeconomic study of medicinal products, the model of formation of the Recommended basic and additional lists of remedies applied for acute simple bronchitis pharmacotherapy in early age children, consisting of seven successive stages, was substantiated and developed. According to the offered model, the Recommended list of the most effective and economically affordable remedies included 24 trade names, including 13 antibacterial, 1 antiviral, 2 immunomodulatory and 8 mucolytic drugs. The share of the national remedies in this list was 20.8 %. Conclusion. The offered Recommended list of the remedies will help to form local formulary and insurance drug list for pharmacotherapy in early age children under conditions of outpatient and clinic health facilities. At the same time, the given List is a basis for prediction of the future needs for necessary medicines and their cost reimbursement calculation for children under 3 years with acute simple bronchitis, which will help to save budget funds